(untitled) (Research, Society and Development, 2019)
Working capital is a fundamental element for the functioning and sustainability of organizations and their inefficient management can lead them to the early termination of their activities. Working capital is the resource used to finance the chronological interval between the timing of payments and the receipt of sales when there is no perfect synchronization between receipts and payments. In this sense, the general objective of this research was to describe and analyze how the management of short-term financial resources of micro and small industries in the foundry sector of Cláudio, MG is performed. In order to achieve this objective, an exploratory and descriptive research of a quantitative nature was carried out, whose data were collected by a questionnaire applied to an intentional sample of fifteen companies that comprised a research universe of 52 companies. It was concluded that the factors that most influenced the management of working capital, from the point of view of financial managers, were the high tax burden, the difficulty to manage costs and the lack of knowledge about financial management tools.